Estudo da carbonatação da camada de cobrimento de protótipos de concreto com altos teores de adições minerais e cal hidratada - Cadore, William Widmar (2008)
In this study deals the covercrete structural concrete layer with the use of hydrated lime in substitution in mass of the sand in ternary mixture of 70% of blast-furnace slag, 20%-fly ash and 10% of cement CPV-ARI (EVC) in comparison to reference with 100% CPV-ARI (R) and other ternary mixture of 70%-ground granulated blast-furnace slag, 20%-fly ash and 10%-cement CPV-ARI without addition of the hydrated lime (EV). Beams prototypes were molded, exposed in environmental curing for the study of the structural concrete covercre layer. The carbonation analysis was made in extracted testimonies at 91st and the 300th days. The depth of the testimonies was the following: layer 1 - 0 to 10 mm, layer 2 - 20 to 30 mm and layer 3 - 45 to 55 mm. The accelerated carbonation tests were accomplished in atmosphere with 5% of CO2 content, following RILEM CPC-18, after pre-conditioning. The analysis of the test results were in comparison of the mixtures with hydrated lime in relation to the mixtures without hydrated lime and the reference mixtures. It was observed that the addition of hydrated lime in the mixtures reduced the carbonated depths and consequently the carbonation coefficients. The presented results indicate that the hydrated lime addition reached the purpose restoring the alkaline reserve, reducing the carbonated dephts so much by the chemical as physical actions. In a general way, R and EV presented tendency of larger coefficients in the most internal layer (C1 < C3) and EVC contrary behavior (C1>C3). It was observed a paradox in resistance equality on concrete types with hydrated lime, with reduction of the coefficients to the 300th days compared to the 91st days. This behavior can be explained by the most compacts and homogeneous structure, since there was connection pores reduction of 50% up to 25nm and C-S-H increases with the age. However, the relationship among the accelerated and natural tests indicate that to the 300th days the accelerated effects process tend to be between 1,5 and 3,5 larger times than the natural tests.